Evaluating efficiency of customized medium density INDUSCHIP for genotyping of Indicine cattle breeds - SAHA, SUJIT; NAYEE, NILESH; SUDHAKAR, A; GAJJAR, SWAPNIL; TRIVEDI, K R; GUPTA, R O; KISHORE, G (The Indian Journal of Animal Sciences, 2021)
To initiate genomic selection programme for indicine cattle breeds and their crosses in India, National Dairy Development Board designed a medium-density (52K) customized chip on Illumina platform named as “INDUSCHIP”. The present study was conducted to examine the efficiency of INDUSCHIP SNP panel for genotyping indicine cattle breeds. Total of 500 animals belonging to 14 different indicine breeds were genotyped with Illumina Bovine HD chip. A subset of SNPs was taken for evaluating the performance of selected SNPs in different indicine breeds. The average minor allele frequency (MAF) was found to vary between 0.20–0.29 for different indicine breeds. However, for important milk breeds like Sahiwal, Gir, Red Sindhi and Kankrej the average MAF was found to be 0.27 and above. Mean Linkage Disequilibrium (LD) at 50–60 kbp distance was found to be around 0.21. There was considerable LD decay with increasing distance between SNPs. Around 0.06% SNPs were found to be significantly deviating from Hardy-Weinberg equilibrium. From the Principal component analysis (PCA) it was found that the first three Principal Components i.e. PC1, PC2 and PC3) could separate different indicine breeds. The present study indicated that due to the presence of highly polymorphic SNPs for the breeds of indicine origin, INDUSCHIP panel was found to be effective and informative in genotyping indicine breeds.